Synthesis and docking studies of 2,4,6-trihydroxy-3-geranylacetophenone analogs as potential lipoxygenase inhibitor - Chean, Hui Ng; Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi; Abas, Faridah; Kok, Wai Lam; Ismail, Intan Safinar; Narayanaswamy, Radhakrishnan; Jamaludin, Fadzureena; Shaari, Khozirah (MDPI, 2014)
The natural product molecule 2,4,6-trihydroxy-3-geranyl-acetophenone (tHGA) isolated from the medicinal plant Melicope ptelefolia was shown to exhibit potent lipoxygenase (LOX) inhibitory activity. It is known that LOX plays an important role in inflammatory response as it catalyzes the oxidation of unsaturated fatty acids, such as linoleic acid to form hydroperoxides. The search for selective LOX inhibitors may provide new therapeutic approach for inflammatory diseases. Herein, we report the synthesis of tHGA analogs using simple Friedel-Craft acylation and alkylation reactions with the aim of obtaining a better insight into the structure-activity relationships of the compounds. All the synthesized analogs showed potent soybean 15-LOX inhibitory activity in a dose-dependent manner (IC50 = 10.31–27.61 μM) where compound 3e was two-fold more active than tHGA. Molecular docking was then applied to reveal the important binding interactions of compound 3e in soybean 15-LOX binding site. The findings suggest that the presence of longer acyl bearing aliphatic chain (5Cs) and aromatic groups could significantly affect the enzymatic activity